2009
DOI: 10.1007/s10327-009-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and pathogenicity of Fusarium oxysporum isolated from wilted Welsh onion in Japan

Abstract: Thirty isolates of Fusarium oxysporum from wilted Welsh onion plants were examined for their diversity in nucleotide sequences of the ribosomal DNA (rDNA) intergenic spacer (IGS) region and for pathogenicity with regard to five Welsh onion cultivars. Phylogenetic analysis based on the IGS sequences revealed polyphyletic origins of the isolates and a relationship between phylogeny and pathogenicity; low virulence isolates differed genetically from those with high and moderate virulence. Mating type analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
(23 reference statements)
3
14
0
1
Order By: Relevance
“…These results agree with previous studies, which showed variation in the virulence of F. oxysporum isolates from rocket (Catti et al 2007;Garibaldi et al 2006), lamb's lettuce ) and onion (Dissanayake et al 2009). Some of the variation in the aggressiveness found in the isolates of the forma specialis raphani cannot be easily linked to the IGS sequencing results.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These results agree with previous studies, which showed variation in the virulence of F. oxysporum isolates from rocket (Catti et al 2007;Garibaldi et al 2006), lamb's lettuce ) and onion (Dissanayake et al 2009). Some of the variation in the aggressiveness found in the isolates of the forma specialis raphani cannot be easily linked to the IGS sequencing results.…”
Section: Discussionsupporting
confidence: 95%
“…According to these researchers, the diversity of the IGS haplotype within F. oxysporum suggests that sexual reproduction is infrequent or absent in this fungus. Recently, Dissanayake et al (2009) reported four different clusters among 30 isolates of F. oxysporum on onion in Japan.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…wäre mittels biochemischer bzw. molekularbiologischer Untersuchungen zu zeigen (Bayraktar et al 2010;galvan et al 2008;bayraktar und Dolar 2011;Swift et al 2002;Dissanayake et al 2009;Özer et al 2003;elZawahry et al 2000).…”
Section: Gewicht (G)unclassified
“…W.C. Snyder & H.N. Hans is one of the most destructive diseases of onion, which cause serious yield losses in Japan, the Netherlands, and the USA (Sumner 1995;Galván et al 2008;Dıssanayake et al 2009). In Turkey, Türkkan and Karaca (2006) found that Fusarium basal rot is a common and severe disease in Amasya province where onions are intensively cultivated.…”
mentioning
confidence: 99%